Review of "A grammar of Kham" - Noonan, Michael (2024)
The excellent grammar under review here, David Watters' A Gram-mar of Kham, is a description of the Takale dialect of the Kham lan¬guage of Nepal, though numerous references are made to other Kham dialects. The book contains a 417 page grammar, 23 pages of tran¬scribed texts, a 14 page dictionary, two maps, and a detailed topic index. The final chapter of the grammar is devoted to a discussion of the Kham verb in historical perspective.